EVIDENCE-BASED NURSING: CHARACTERISTICS OF STUDIES IN BRAZIL - Karilena Karlla Amorim Pedrosa; Isabelle Christine Marinho Oliveira; Alexsandra Rodrigues Feijão; Regimar Carla Machado (Universidade Federal do Paraná, 2015)
The purpose of this integrative review was to characterize Brazilian studies on the practice of evidence-based nursing practice. The literature search was carried out between June and September 2014 in the Latin American and Caribbean Health Science Literature Database, the Scientific Electronic Library Online, and the National Library of Medicine National Institutes of Health. Twenty-one articles were selected, all published in Brazilian journals between 2003 and 2004. The results indicate a greater number of level 5 reviews in comparison to other types of studies. Of these, most were integrative and systematic reviews directed at healthcare and teaching practices, developed in the Southeast of Brazil, by nursing professors who have a doctoral degree as their highest qualification. In conclusion, nurses in the healthcare context must be trained to search for, develop and use research in practical contexts in order to overcome the dichotomy between research and healthcare provision.